Análisis comparativo de multifónicos en la familia de saxofones (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2022)
This work presents a comparative analysis of multiphonics in the different members of the saxophone family. Starting from the intuitive premise that the same fingering on two different saxophones would result in the same multiphonic but transposed, 18 examples were analysed from two different perspectives: 1) multiphonics with the same fingering on different saxophones; 2) multiphonics with the same notes (sounding pitches) but different fingerings on different saxophones. In both cases, the study involved spectral analysis of a set of multiphonics specially selected for their particular characteristics, including a transcription to musical notation of the main spectral components. As a complement, the spectral analysis of similar multiphonics were compared, focusing on saxophones that share the same tuning (soprano and tenor saxophones in Bb, alto and baritone in Eb). The results obtained in this work, allow us to open research questions for the future, mainly considering timbre perception of those multiphonics that, sharing the same spectral structure, present amplitude variations in the pitch components between saxophones.
Keywords: multiphonics; saxophone; spectral analysis; timbre